2017
DOI: 10.5858/arpa.2017-0214-ra
|View full text |Cite
|
Sign up to set email alerts
|

Localization for Breast Surgery: The Next Generation

Abstract: Context.— Preoperative localization of nonpalpable breast lesions using image-guided wire placement has been a standard of breast imaging, diagnosis, and treatment since its development in the 1970s. With this technique, coordinated, same-day wire placement by the radiologist and surgery are required, which can lead to significant inefficiencies in workflow. Other disadvantages of wire localization (WL) include limitations in surgical incision and dissection route and protruding wires that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 13 publications
0
68
0
Order By: Relevance
“…Advantages of the seed include that there is no risk of displacement of a protruding wire, and the seed can be placed days prior to surgery, reducing delays in operating room start times ii . Disadvantages to the seed include requirements for strict adherence to nuclear regulations, training of all personnel who handle the seed in radiation safety, obtaining proper licensing, and meticulous tracking and disposal of the seed …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advantages of the seed include that there is no risk of displacement of a protruding wire, and the seed can be placed days prior to surgery, reducing delays in operating room start times ii . Disadvantages to the seed include requirements for strict adherence to nuclear regulations, training of all personnel who handle the seed in radiation safety, obtaining proper licensing, and meticulous tracking and disposal of the seed …”
Section: Introductionmentioning
confidence: 99%
“…Disadvantages to the seed include requirements for strict adherence to nuclear regulations, training of all personnel who handle the seed in radiation safety, obtaining proper licensing, and meticulous tracking and disposal of the seed. 4 In 2014, the FDA approved the first nonradioactive nonwire localization device, the Savi Scout ® Radar (Cianna Medical, Inc). This system uses radar reflector activated with infrared light, which is detected by a console which generates a signal that is detectable by a radar detector probe.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies have shown better cosmetic results, no significant difference for negative margin rates and schedule improvement compared to the WGL [3][4][5][6]. However the RSL is radioactive; therefore the manipulation of radioactive material requires a specialized structure and organization, from localization to excision, including transport, storage and elimination, increasing costs, and bringing constraints to diffusion of this technique [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, the FDA approved SAVI SCOUT radar localization system [8][9][10], a 12-mm non-radioactive seed detected by an infrared light probe. The device could be placed 30 days before surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The Magseed system received FDA approval in 2016 and has been shown to be an effective alternative to traditional wire‐guided localization. A nonradioactive paramagnetic seed is placed at the site of a breast lesion with either sonographic or mammographic guidance prior to surgery . The Sentimag probe is then used intraoperatively to detect the magnetic marker.…”
mentioning
confidence: 99%